2011
DOI: 10.1007/s10237-011-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Tenocyte contraction induces crimp formation in tendon-like tissue

Abstract: Tendons are composed of longitudinally aligned collagen fibrils arranged in bundles with an undulating pattern, called crimp. The crimp structure is established during embryonic development and plays a vital role in the mechanical behaviour of tendon, acting as a shock-absorber during loading. However, the mechanism of crimp formation is unknown, partly because of the difficulties of studying tendon development in vivo. Here, we used a 3D cell culture system in which embryonic tendon fibroblasts synthesise a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 40 publications
8
62
0
Order By: Relevance
“…The reason for buckling is not fully understood but is most likely the result of local breakage of collagen fibrils with concomitant contraction of the actinomyosin cytoskeleton. Recent studies using a tendon-like construct system showed that cells exert forces on the surrounding extracellular matrix (Herchenhan et al, 2012, Kalson et al, 2013). In the absence of sufficient restraining force in the matrix (as might occur if a small but significant number of fibrils are severed) cell contraction can result in matrix buckling and nucleus shape changes.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for buckling is not fully understood but is most likely the result of local breakage of collagen fibrils with concomitant contraction of the actinomyosin cytoskeleton. Recent studies using a tendon-like construct system showed that cells exert forces on the surrounding extracellular matrix (Herchenhan et al, 2012, Kalson et al, 2013). In the absence of sufficient restraining force in the matrix (as might occur if a small but significant number of fibrils are severed) cell contraction can result in matrix buckling and nucleus shape changes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity and variability in these tissues, the literature is inconsistent for material parameters and geometries. However, some meaningful ranges are provided by Herchenhan et al [32], and ranges for fibril volume fraction can be found in studies by Lavagnino et al [34]. Limited information is available on the sensitivity of these models to a variation in fibril and matrix volume fractions V f and V m , fibril average diameter d 0 , fibril Young's and shear moduli E f and G f , matrix Young's and shear moduli E m and G m , and stress transfer length k c .…”
Section: Modeling Of a 2d Simplified Tendon Comprised Of 100mentioning
confidence: 99%
“…Table 1 lists the parameter values used for the current application as determined from the literature and from the sensitivity analysis starting from the reference ranges provided in Ref. [32].…”
Section: Modeling Of a 2d Simplified Tendon Comprised Of 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, very few multiscale models have been developed and used to study tendon properties across different length scales. In one example, a computational cell composed of hyperelastic fibril bundles, interfibrillar matrix and embedded tenocytes was created, and FE analyses were conducted to investigate the cause of crimp in tendon [144,145]. In this study, shear stresses on the interface between collagen fibrils and interfibrillar matrix-attributed to cell contraction-caused crimp structure, and the ratio of fibrils to interfibrillar matrix determined crimp length [144].…”
Section: Computational Modelling Using Multiscale Approaches 331 Mmentioning
confidence: 99%